Microalgas (Chlorella sorokiniana) no tratamento de sementes de soja: inoculação e coinoculação - Barbosa, Jéssica Zanelatto (2024)
Microalgae are potential sources of bioproducts for applications in several areas. In agriculture, they appear as a promising option as biostimulants, providing greater yield. Consequently, the objective of this study was to evaluate the effect of the microalgae Chlorella sorokiniana (strains IPR7104 and IPR70) with Bradyrhizobium japonicum in inoculation and coinoculation as a biostimulant of soybean agronomic parameters. Two experiments were conducted, one in a greenhouse and the other under field conditions at the experimental station of the Institute of Rural Development of Paraná, located in Santa Tereza do Oeste, PR. In a greenhouse, an emergency test was carried out to evaluate the biostimulant potential of the microalgae Chlorella sorokiniana on the seeds and in the field, to evaluate production components and chlorophyll levels. Six treatments were evaluated: control (without inoculation); inoculant only (Bradyrhizobium japonicum); supernatant from microalgae cultivation (strain IPR 7070) + inoculant (Bradyrhizobium japonicum); pellet from microalgae cultivation (strain IPR 7070) + inoculant (Bradyrhizobium japonicum); supernatant from microalgae cultivation (strain IPR 7104) + inoculant (Bradyrhizobium japonicum) and pellet from microalgae cultivation (strain IPR 7104) + inoculant (Bradyrhizobium japonicum). In the field, in addition to these, another treatment was evaluated, without inoculant (Bradyrhizobium japonicum) and with nitrogen fertilizer applied as top dressing. The design used was randomized blocks, with five replications. The emergence and dry matter production of seedlings, total chlorophyll content in leaves, nodule count, dry mass production of nodules, dry matter production of shoots and grain productivity were analyzed. Microalgae Chlorella sorokiniana (strains IPR7104 and IPR 7070) did not demonstrate biostimulant potential when applied as a seed treatment in soybean crops, isolated or in coinoculation with Bradyrhizobium japonicum.